Pengembangan Media Pembelajaran Multiplatform Simulasi Instalasi Sistem Operasi Menggunakan Unity Engine: Development of Multiplatform Learning Media for Operating System Installation Simulation Using Unity Engine - Riana T. Mangesa; Muhammad Fadhil Hisyam; Edi Suhardi Rahman (Jurnal Pendidikan Terapan, 2025)
This study aims to determine the validation results of developing a multiplatform learning media for Operating System Installation Simulation using Unity Engine, to understand user feedback on the developed multiplatform learning media for Operating System Installation Simulation using Unity Engine, and to evaluate the effectiveness of the developed multiplatform learning media. This research follows a Research and Development (R&D) approach, utilizing the ADDIE model for media development. Data collection techniques include interviews, questionnaires, documentation, and tests. The outcome is a learning media product for simulating the installation of the Windows 10 operating system, available on multiple platforms specifically Windows desktop and Android mobile offering a feasible, highly effective tool for learning. The feasibility of this learning media was assessed based on validation results from media and subject matter experts, which indicated a feasible rating. User responses in both small and large groups were highly positive. The effectiveness test showed a classical completion rate above the standard, with average simulation times closely matching real-case scenarios, affirming the effectiveness of this learning media.